Rządowa promocja eksportu małych i średnich firm. Doświadczenia zagraniczne i propozycje dla Polski - Krzykała-Schaefer, Renata (Wydział Prawa i Administracji UAM, 1993)
A governmental promotion of export of in market economy countries is the form of t he activity of t h e state, which, on one hand, takes steps to safeguard a smooth course of economic and social processes, and, on the other, aims at securing for itself an advantageous market position in conditions of increased international competition. The promotion of export of small and medium companies is specific as to its character and scope. It must take into account characteristic features of such firms, their problems and potential, main motives of their operation and main risks. Governments of developed countries grant special protection to small and medium firms, for such firms play special role in the economy through their flexibility and dynamism, their contribution to the development of innovative activity and new technologies, as well as their contribution to export-oriented restructuring of t h e state economy and the improvement of competitiveness.
Governmental protection of export of small and medium companies. Foreign experience and proposals for Poland